2004
DOI: 10.1016/j.cell.2004.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Thermotolerance Requires Refolding of Aggregated Proteins by Substrate Translocation through the Central Pore of ClpB

Abstract: Cell survival under severe thermal stress requires the activity of the ClpB (Hsp104) AAA+ chaperone that solubilizes and reactivates aggregated proteins in concert with the DnaK (Hsp70) chaperone system. How protein disaggregation is achieved and whether survival is solely dependent on ClpB-mediated elimination of aggregates or also on reactivation of aggregated proteins has been unclear. We engineered a ClpB variant, BAP, which associates with the ClpP peptidase and thereby is converted into a degrading disag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
507
3
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 443 publications
(535 citation statements)
references
References 41 publications
22
507
3
3
Order By: Relevance
“…The mechanism of ATPase activation by casein or polylysine is not known, but it is accepted that the ATPase acceleration accompanies translocation of the soluble pseudosubstrates through the channel of ClpB. 9 Thus, our results suggest that the translocation machinery may remain functional in the ClpB variants with the noncanonical Walker A motif.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…The mechanism of ATPase activation by casein or polylysine is not known, but it is accepted that the ATPase acceleration accompanies translocation of the soluble pseudosubstrates through the channel of ClpB. 9 Thus, our results suggest that the translocation machinery may remain functional in the ClpB variants with the noncanonical Walker A motif.…”
Section: Resultsmentioning
confidence: 64%
“…[6][7][8] The ClpB activity is linked to extraction of single polypeptides from aggregated particles and their forced unfolding by translocation through a narrow channel located at the center of the hexameric ring. 9 The substrate translocation by ClpB is driven by ATP hydrolysis and is analogous to the degradationpreceding unfolding/translocation of substrates by the proteasome and other ATP-dependent proteases. 10 Aggregated substrates bind to D1 and to the N-terminal domain of ClpB, 11,12 become translocated through the channel from D1 to D2, then exit the ClpB oligomer and their further folding in solution may be assisted by other chaperones.…”
Section: Introductionmentioning
confidence: 99%
“…All Hsp100s self-assembly into ring-shaped structures and conformational changes are triggered by ATP binding and hydrolysis, which changes the positions of bound substrates relative to each other, followed by the translocation of the polypeptide through the central channel during aggregate reactivation (Weibezahn et al 2004, Zolkiewski 2006. By using E. coli ClpB as a model, Schlieker et al (2004) showed that the disaggregation mechanism involves continuous extraction of unfolded proteins from the aggregate that are solubilized into the central channel in a process called "threading".…”
mentioning
confidence: 99%
“…Likewise, the hexameric structure of ClpB from Thermus thermophilus (Fig. 1b) is crucial for its activity because it provides multiple sites for polypeptide substrate binding, which are translocated through its central channel during aggregate reactivation (Schirmer et al 1996, Lee et al 2003, Schlieker et al 2004, Weibezahn et al 2004, Zolkiewski 2006, Barends et al 2010, Mayer 2010, Zolkiewski et al 2012, Doyle et al 2013). The solubilized protein can then be refolded either spontaneously, or by a chaperone network independent of ClpB.…”
mentioning
confidence: 99%
“…ATP is bound at the interface between adjacent subunits 12 and hexamerization is stabilized by nucleotide 13, 14 . Substrate binding occurs when the hexamer is in its ATP-bound conformation and conserved pore residues may contact substrates directly [15][16][17] . The N-and C-terminal domains may also help engage substrates and co-factors 18,19 .…”
mentioning
confidence: 99%